DNA methylation profiling in human lung tissue identifies genes associated with COPD. Issue 10 (2nd October 2016) - Morrow, Jarrett D.; Cho, Michael H.; Hersh, Craig P.; Pinto-Plata, Victor; Celli, Bartolome; Marchetti, Nathaniel; Criner, Gerard; Bueno, Raphael; Washko, George; Glass, Kimberly; Choi, Augustine M. K.; Quackenbush, John; et al.
ABSTRACT: Chronic obstructive pulmonary disease (COPD) is a smoking-related disease characterized by genetic and phenotypic heterogeneity. Although association studies have identified multiple genomic regions with replicated associations to COPD, genetic variation only partially explains the susceptibility to lung disease, and suggests the relevance of epigenetic investigations. We performed genome-wide DNA methylation profiling in homogenized lung tissue samples from 46 control subjects with normal lung function and 114 subjects with COPD, all former smokers. The differentially methylated loci were integrated with previous genome-wide association study results. The top 535 differentially methylated sites, filtered for a minimum mean methylation difference of 5% between cases and controls, were enriched for CpG shelves and shores. Pathway analysis revealed enrichment for transcription factors. The top differentially methylated sites from the intersection with previous GWAS were in CHRM1, GLT1D1, and C10orf11 ; sorted by GWAS P -value, the top sites included FRMD4A, THSD4, and C10orf11 . Epigenetic association studies complement genetic association studies to identify genes potentially involved in COPD pathogenesis. Enrichment for genes implicated in asthma and lung function and for transcription factors suggests the potential pathogenic relevance of genes identified through differential methylation and the intersection with a broader range of GWAS associations.